Case series: Reinfection of recovered SARS CoV‐2 patients for the third time - Sepideh Hasanzadeh (Wiley, 2021)
Abstract This set of cases provides important evidence of re‐infection and recurrence of SARS‐CoV‐2 even for the third time. Consequently, this possibility should be considered more in recurrent patients with Covid‐19 symptoms.